2013
DOI: 10.1007/s10578-013-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-Promoting Parenting Behaviors: A Comparison of Anxious Mothers and Fathers

Abstract: The majority of research identifying anxiety-promoting parenting behaviors has been conducted with mothers, leaving a gap in current knowledge about the role of fathers’ parenting behaviors. In an attempt to fill this gap, this study compared anxiety-promoting parenting behaviors of anxious mothers and fathers. Parents completed self-report measures of parenting behavior and independent coders rated parenting behaviors (i.e., overcontrol, granting of autonomy, warmth, hostility, anxious behavior) of mothers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
(66 reference statements)
2
38
0
Order By: Relevance
“…Lamontagne et al demonstrated high anxiety scores in the children of parents; who also had increased anxiety levels preoperatively [15]. It was suggested that children experienced lower anxiety levels if less anxious parents accompanied them [16] [17]. In our study, mothers had higher preoperative STAI-S scores than fathers.…”
Section: Discussionsupporting
confidence: 54%
“…Lamontagne et al demonstrated high anxiety scores in the children of parents; who also had increased anxiety levels preoperatively [15]. It was suggested that children experienced lower anxiety levels if less anxious parents accompanied them [16] [17]. In our study, mothers had higher preoperative STAI-S scores than fathers.…”
Section: Discussionsupporting
confidence: 54%
“…Evidence for this hypothesis derives from large national studies of the A-B connection showing that poor marital adjustment (high conflict, low satisfaction) is associated with depression and anxiety in men and women (McShall & Johnson, 2015;Whisman, Robustelli, & Labrecque, 2018). Completing the second leg of a mediation analysis B-C), studies show that parental depression and anxiety are consistently linked with parenting behavior that is harsh, intrusive, or distant (Lovejoy, Graczyk, O'Hare, & Neuman, 2000;Teetsel, Ginsburg, & Drake, 2014). The question, then, is whether either or both of these two paths also explain links between high couple conflict and anxious or harsh parenting (A-C).…”
Section: An Alternative Mediation Hypothesismentioning
confidence: 99%
“…Fathers may emphasize independence and challenge their children more than mothers (Bögels & Phares, 2008), and they have been shown to display more overcontrol (completing a task, directing child actions) than mothers during more neutral parent-child interactions (Teetsel, Ginsburg, & Drake, 2014). Finally, this initial work on understanding the ETAN dimension focused on establishing it as a meaningful way to conceptualize certain parenting behaviors with inhibited toddlers.…”
Section: Discussionmentioning
confidence: 99%